जुम्लाको उच्च पहाडी क्षेत्रको रैथाने रातो कोदोको मूल्याङ्कन, दर्ता तथा प्रवद्र्धन - Thapa, Pradip; Pudasaini, Niranjan; Parajuli, Kabita Jaishi; Joshi, Balkrishna (Genetics, Plant Breeding and Seed Science, 2025)
The finger millet landrace 'Rato Kodo' (Eleusine coracana L.), traditionally cultivated in Jumla district of Nepal, was evaluated through participatory plant breeding approaches under the Local Crop Project supported by GEF/UNEP. Morphological characterization, productivity assessment, and farmers’ preferences were documented through field trials and community discussions. The landrace demonstrated superior agronomic traits including early maturity, higher finger count per ear, and notable grain yield (130–165 kg/ropani). Compared to Kalo Kodo (black millet), Rato Kodo (red millet) exhibited better adaptability and yield potential under high-hill conditions. Based on its performance and socio-cultural value, it was officially registered by the National Seed Board in 2020, becoming the highest altitude recommended millet variety in Nepal. The genotype is now conserved at the National Genebank (NGRC05113) and promoted for seed production through local seed banks. This case illustrates the value of participatory varietal selection and community-led conservation for climate-resilient mountain agriculture.